A new double radio relic in PSZ1 G096.89+24.17 and a radio relic mass–luminosity relation. Issue 4 (13th September 2014) - de Gasperin, F.; van Weeren, R. J.; Brüggen, M.; Vazza, F.; Bonafede, A.; Intema, H. T.
Abstract : Radio relics are diffuse synchrotron sources in galaxy clusters that are believed to trace large-scale shock waves. We have discovered a new double radio relic system in PSZ1 G096.89+24.17 ( z  = 0.3) and have carried out a full-polarization radio observation using the Westerbork Synthesis Radio Telescope at 1.4 GHz. The observation revealed the presence of two relics located on the two diametrically opposite sides of the cluster and hints of a central radio halo. The linear sizes of the relics are ∼0.9 and ∼1.4 Mpc. We carried out an analysis of all known double radio relics by using radio, X-ray and Sunyaev–Zel'dovich data. We find that the radio luminosity of double relics is a steep function of the cluster mass, with L R ∝ M 2.83 ± 0.39 . If we include single radio relics, this relation is maintained. This dependence has implications for the origin of magnetic fields at the relic's locations.